The Case for Tutoring Struggling Readers in the Primary Grades. Issue 2 (4th March 2023) - Morris, Darrell
Abstract: Over the past 50 years, our schools have failed to teach a large portion (one-third) of students to read at a basic level by the end of fourth grade. After presenting evidence of this reading education problem and overviewing historical attempts to address it, I argue that serious, one-to-one tutoring initiatives offer the best chance for meaningful change. I use a detailed case study to show how a school could mount an effective one-to-one tutoring program for at-risk readers in grades 1–3. The key factor is an expert reading teacher who is willing to supervise the tutoring efforts of teacher assistants, paraprofessionals, and possibly community volunteers. Standing in the way of such an evidence-based approach is cost and, relatedly, a school culture that has relied on recurring changes in classroom teaching methods, as opposed to intensive one-to-one instruction, to address early reading failure.